ANALYSIS OF POLITICAL, SOCIO-ECONOMIC AND SPIRITUAL REFORMS IN THE YEARS OF INDEPENDENCE - Mukhriddin Umariy (Modern American Journals, 2025)
The article analyzes the 34-year development path of Uzbekistan's independence, the results of political, socio-economic and spiritual reforms implemented in our country. The creative work, achievements in the fields of education and culture, the expansion of freedom of speech and religion, and the opportunities created for young people during the years of independence are widely covered. It also discusses the role of preserving national values, ensuring peace and tranquility in the stability of society, and the responsibility of the younger generation in growing up as a well-rounded person.
Keywords: Uzbekistan, independence, development, creativity, socio-economic reforms, education, culture, values, peace, youth, prosperity, spirituality.